PROSPECT OF OLIGOPOLY MARKET IN DIGITAL ECONOMY - Frida Yanti Sirait; Mulyana Fitri; Tsamara Balqis; Isnaini Harahap (Proceeding International Seminar of Islamic Studies, 2023)
In terms of marketing company products and services, e-commerce has a significant impact on the industry as a whole, especially in the process of achieving the company's target market. The aim of this research is to present prospect of oligopoly market in digital economy, The method used in this research is literature review. This type of research is quantitative research which is flexible and open to modification by the author according to the needs of the author .The Result One form of oligopolii market that has a huge opportunity is the e-commerce market. Performance in e-commerce companies, which have recently grown rapidly, has not shown any real gains. In five to ten years, this fairly young effort will pay off. It is estimated that the development of this e-commerce market will continue to increase. Although currently there are still not many users due to the fact that only a handful of Indonesians shop online, The practice of oligopoli is considered to be one of the most common methods for assisting individuals and organizations in achieving their goals by determining the appropriate price, which means that the average price between the individuals and organizations that practice oligopoli does not exist.